Low dose ionizing radiation produces too few reactive oxygen species to directly affect antioxidant concentrations in cells - Smith, J. T. (The Royal Society, 2012)
It has been hypothesized that radiation-induced oxidative stress is the mechanism for a wide range of negative impacts on biota living in radioactively contaminated areas around Chernobyl. The present study tests this hypothesis mechanistically, for the first time, by modelling the impacts of radiolysis products within the cell resulting from radiations (low linear energy transfer β and γ), and dose rates appropriate to current contamination types and densities in the Chernobyl exclusion zone and at Fukushima. At 417 µGy h(−1) (illustrative of the most contaminated areas at Chernobyl), generation of radiolysis products did not significantly impact cellular concentrations of reactive oxygen species, or cellular redox potential. This study does not support the hypothesis that direct oxidizing stress is a mechanism for damage to organisms exposed to chronic radiation at dose rates typical of contaminated environments.